Komparasi Kuliner Seblak Tradisional dan Seblak Modern - Ajeng Sukma Sakyamuni; Felice Ariel Tjendrawan; Jusraidil Jusraidil; Nadine Marvella Iputri (Ideas Publishing, 2025)
Seblak is a traditional food from West Java that has undergone a significant transformation from a simple traditional street snack into an urban culinary icon in Indonesia. This study aims to understand how seblak developed from its traditional form based on boiled cracker chips into modern seblak with various flavor options, toppings, and increasingly creative and appealing serving methods. The main issues examined include changes in cultural values, public perceptions of the social status of traditional food, and the economic impact generated by the commercialization of modern seblak within the context of the culinary industry. The research employed a qualitative method with a comparative analysis approach through direct observation of seblak selling practices, accompanied by document analysis such as articles, archives, and promotional materials related to the development of traditional and modern seblak. The results of the study indicate that innovation in taste, packaging, and marketing strategies plays an important role in expanding the market segment, especially among teenagers and urban communities that prioritize practicality. Seblak is no longer regarded as a food for the lower class, but has transformed into a creative culinary product that reflects the ability of Sundanese people to adapt to changes in time and consumption trends. This study concludes that seblak plays an important role in maintaining the existence of local cultural identity while also contributing to the growth of the increasingly competitive and sustainable regional creative economy